2004
DOI: 10.7326/0003-4819-140-5-200403020-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Ottawa Knee Rule To Rule Out Knee Fractures

Abstract: A negative result on an Ottawa knee rule test accurately excluded knee fractures after acute knee injury. However, because the rule is calibrated toward 100% sensitivity and actual fracture prevalences are usually low, large-scale, multicentered studies are still needed to establish the cost-effectiveness of routinely implementing the rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 14 publications
1
45
0
4
Order By: Relevance
“…46 Dowling concluded that the Ottawa ankle rule can be used in the pediatric population (>5 years) to rule out fractures. 47 Bachmann et al 48 also validated the Ottawa knee rule in 2004. The Ottawa knee rule consists of answering five questions asking whether the patient is above 55 years of age, has isolated tenderness of the patella, has tenderness over the head of the fibula, is unable to flex the knee to 90°, and is unable to bear weight for four steps.…”
Section: History and Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Dowling concluded that the Ottawa ankle rule can be used in the pediatric population (>5 years) to rule out fractures. 47 Bachmann et al 48 also validated the Ottawa knee rule in 2004. The Ottawa knee rule consists of answering five questions asking whether the patient is above 55 years of age, has isolated tenderness of the patella, has tenderness over the head of the fibula, is unable to flex the knee to 90°, and is unable to bear weight for four steps.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…Bachmann concluded that the Ottawa knee rule is useful for excluding fracture; however, they did recommend further large-scale testing for validation because they prefer sensitivities above 98.5%. 48 The studies of upper extremity fractures that were identified based on the inclusion criteria focused on elbow or wrist injuries. Figures 2-6 depict forest plots of the sensitivities, specificities, positive LR, and negative LR of history and physical examination in all of the included trials.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…9,22,30,32,45,59,65,68 The intent of this education is to reduce the uncertainty inherent in clinical practice by defining how to use examination findings to make decisions about which course of action to take with specific patients. 71 For instance, during the typical patient examination performed by physical therapists, historical information, and baseline physical examination findings are obtained, which include ambulatory ability, motion and functional limitations, palpation and clinical diagnostic tests (orthopaedic special tests).…”
Section: Evidence Of Competency Within Musculoskeletal Medicine and Ementioning
confidence: 99%
“…For this purpose, it is important that such CPRs have high sensitivity. Metaanalysis of validation studies show these rules achieve high sensitivity that is comparable to the Alvarado score at a cut-off of five points (ankle rule -97.6% [48], knee rule -98.5% [49] and Alvarado score at cut-off of five points -99%).…”
Section: Discussionmentioning
confidence: 99%